Aktivitas Antibakteri Isolat Jamur Endofit Kitolod (Hippobroma longiflora (L.) G. Don.) terhadap Bakteri Escherichia coli dan Staphylococcus aureus - Pramesta, Carerina Oktavia; Syaifudin, Andang; Kusumarini, Niken (Mahesa Research Center, 2025)
Endophytic fungi are microorganisms that inhabit plant tissues without causing harm to their hosts. Hippobroma longiflora (L.) G. Don (kitolod) is known to contain secondary metabolites with antibacterial potential. This study aimed to isolate and evaluate the antibacterial activity of endophytic fungi from the leaves and flowers of kitolod against Escherichia coli and Staphylococcus aureus. Isolation was performed by surface sterilization using 1% NaOCl, 70% ethanol, and sterile water, followed by cultivation on PDA medium. Nine isolates were obtained, consisting of four from flowers and five from leaves. Extracts from PDB cultures were tested using the disc diffusion method (30 µL/disc). Results showed that isolate BK1 exhibited strong antibacterial activity against S. aureus (11.16 mm) and moderate activity against E. coli (9.71 mm). Isolates BK3 and DK3 also displayed strong inhibition zones. The positive control (chloramphenicol) produced very strong inhibition, while the negative control (sterile water) showed none. The antibacterial activity is presumed to originate from secondary metabolites of endophytic fungi, indicating their potential as natural antibacterial sources. Further studies are needed to determine MIC values and conduct molecular identification of the selected isolates.